1992
DOI: 10.1007/bf02165144
|View full text |Cite
|
Sign up to set email alerts
|

Vergleichende Untersuchung zur Möglichkeit der Dosisreduzierung von Fernröntgenseitenaufnahmen

Abstract: Thanks to their capability for post-processing of image data, the digital radiological techniques introduced from 1970 onwards permit dose reduction with no loss of clinical information. The aim of this study was to establish the extent of possible dose reduction in orthodontic lateral cephalography. For this purpose, lateral cephalograms of a head phantom taken with varying radiation doses (5 to 150 mAs, constant 70 kV) were evaluated. The evaluations of ten judges were compared statistically. Conventional la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
4

Year Published

1996
1996
2001
2001

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 21 publications
1
9
0
4
Order By: Relevance
“…The use of cephalostats provided a clear-cut increase in the reproducibility of the radiographs [3]. The insertion of wedge-shaped aluminium filters into the radiation beam in the region of the anterior facial soft tissues or the use of special dispersion foils [16] permitted better visualization of the facial soft tissues. Besides efforts to improve the quality of the images, the focus was increasingly on reducing the radiation exposure, so that a broad range of technical innovations aimed at reducing the exposure was introduced into the clinical routine.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The use of cephalostats provided a clear-cut increase in the reproducibility of the radiographs [3]. The insertion of wedge-shaped aluminium filters into the radiation beam in the region of the anterior facial soft tissues or the use of special dispersion foils [16] permitted better visualization of the facial soft tissues. Besides efforts to improve the quality of the images, the focus was increasingly on reducing the radiation exposure, so that a broad range of technical innovations aimed at reducing the exposure was introduced into the clinical routine.…”
Section: Discussionmentioning
confidence: 99%
“…With the increasing systematic use of lateral cephalograms, attention is being directed more and more to questions of radiation protection. As most orthodontic patients are children or adolescents, even greater consideration has to be given to keeping radiation exposure to a minimum [16]. Current doses for lateral cephalograms are 0.05 to 1.1 mSv, to which exposure to natural radiation sources amounting to about 2 mSv per year has to be added [13].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown the adequate diagnostic value of digital cephalograms [7,[15][16][17]. Half of the patients were randomly assigned to conventional X-ray technique (film-screen system) and the other half to digital luminescence radiography.…”
Section: Methodsmentioning
confidence: 99%